The Role of ADC‐Based Thermometry in Measuring Brain Intraventricular Temperature in Children. Issue 3 (26th December 2015) - Wagner, Matthias W.; Stern, Steven E.; Oshmyansky, Alexander; Huisman, Thierry A. G. M.; Poretti, Andrea
ABSTRACT: BACKGROUND AND PURPOSE: To determine the feasibility of apparent diffusion coefficient (ADC)‐based thermometry to assess intraventricular temperature in children. METHODS: ADC maps were generated from diffusion tensor imaging data, which were acquired with diffusion gradients along 20 noncollinear directions using a b ‐value of 1000 s/mm 2 . The intraventricular temperature was calculated based on intraventricular ADC values and the mode method as previously reported. The calculated intraventricular temperature was validated with an estimated brain temperature based on temporal artery temperature measurements. We included 120 children in this study (49 females, 71 males, mean age 6.63 years), 15 consecutive children for each of the following age groups: 0‐1, 1‐2, 2‐4, 4‐6, 6‐8, 8‐10, 10‐14, and 14‐18 years. Forty‐three children had a normal brain MRI and 77 children had an abnormal brain scan. Polynomial fitting to the temperature distribution and subsequent calculation of mode values was performed. A correlation coefficient and a coefficient of determination were calculated between ADC calculated temperatures and estimated brain temperatures. Linear regression analysis was performed to investigate the two temperature measures. RESULTS: ADC‐based intraventricular temperatures ranged between 31.5 and 39.6 °C, although estimated brain temperatures ranged between 36.3 and 38.1 °C. The difference between the temperatures is larger for children with more than 8, 000 voxels within the lateral ventricles compared to children with less than 8, 000 voxels. The correlation coefficient between ADC‐based temperatures and the estimated brain temperatures is .1, the respective R 2 is .01 indicating that 1% of the changes in estimated brain temperatures are attributable to corresponding changes in ADC‐based temperature measurements ( P = .275). CONCLUSIONS: ADC‐based thermometry has limited application in the pediatric population mainly due to a small ventricular size.